The RAF and the German Question: Armed Struggle from the Patriotic Revolutionarism - Almeida Díez, Adrián (Hispania Nova, 2022)
This present article wants to offer a framing analysis produced by the west-German armed group, Red Army Faction (RAF). From the study of different theoretical approaches of this violent collective, we try to prove the hypothesis that the RAF was close to the principles of the Patriotic Revolutionarism. Therefore, we want to correct tentatively the common insertion of this group under the category of social-revolutionary terrorism. In addition, we try to show how the hybrid ideology of the RAF became and how, this last element, could have been decisive in order to understand the uses of the violence within the German group.